Balloon dilation of the eustachian tube using endovascular balloon under local anesthesia—a case series and systematic literature review - Ungar, Omer J.; Demir Bajin, Münir; Dahm, Valerie; Lin, Vincent Y. W.; Chen, Joseph M.; Le, Trung N. (Frontiers in Surgery, 2024)
Objective: To report a novel technique in Balloon Dilation of Eustachian Tube (BDET) using an endovascular balloon (EVB), in a prospective cohort. The results are compared with reported outcomes using standard balloons.Methods: Demographic information and clinical parameters were collected prospectively fora series of patients with obstructive eustachian tube dysfunction (OETD). Balloon dilation Eustachian tuboplasty was performed under local anesthesia in a tertiary referral center, using the EVB. Systematic literature review was used for comparison, using Medline via "PubMed", "Embase", and "Web of Science".Results: Eight OETD candidates (12 ears) were enrolled; 5 males and 3 females. Average age was 48 (range -23 to 63) years. The most common presenting symptom was aural fullness (9/12), followed by ear pressure (7/12), hearing loss (5/12) and tinnitus (4/12). Otoscopically, tympanic membrane retraction was evident in 10/12 ears, the majority of which was class II -Sade classification. Pre-operative tympanogram was type B and C in 7 and 5 ears, respectively. All BDETs were performed without complications. Post-operative tympanometry was A in 8/12 ears. Post-operatively, Eustachian Tube Dysfunction Questionnaire-7 results reduced to within normal limits (average score ≤3) in 11/12 ears (p=0.0014). The systematic literature review included 6 papers (193 patients, 262 ETs) with comparable results, most also with little adverse effects.BDET using an EVB is a safe and effective option for OETD. It is well tolerated under local anesthesia in properly selected individuals. The reduced procedural cost may be an important factor in certain healthcare jurisdictions.